PENGARUH KEPEMIMPINAN, DISIPLIN, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi pada Badan Kepegawaian Daerah Provinsi Jawa Tengah) - Novitasari Dyah Hatiningrum, 14.05.51.0086; Murdiyanto, Agus (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the influence of leadership, dicipline and work motivation on the employees performance in Badan Kepegawaian Daerah Provinsi Jawa Tengah. Respondents from the study consist of 78 people in Badan Kepegawaian Daerah Provinsi Jawa Tengah. Model of analysis of the data used was test validity with KMO, reliability testing with Cronbach Alpha and multiple linear regression as using software IBM SPSS version 20,0 to examine and prove research hypothes. Data collected after the test results all data stated is valid and reliable. The finding of the research are : (1). Leadership has no significant and effect employees performance, (2). Dicipline has a positive and significant effect employees performance, and (3). Work motivation has a positive and significant effect employees performance. Keyword : Leadership, Dicipline, Work motivation, Employees performance